343 Dupilumab efficacy on itch and skin lesions in adult patients with prurigo nodularis may be observed concurrently or independently over 24 weeks: results from two phase 3 trials. (25th January 2023) - Kwatra, Shawn G; Yosipovitch, Gil; Ständer, Sonja; Mendes-Bastos, Pedro; Tsai, Tsen-Fang; Nakajima, Saeko; Praestgaard, Amy; Bansal, Ashish; Martinčová, Renata; Levit, Noah A; Wiggins, Simmi
Abstract: Prurigo nodularis (PN) is a chronic inflammatory and pruritic skin disease. Clinically it is characterized by intense pruritus accompanied by hyperkeratotic nodules often associated with a very low quality of life including sleep disruption. The FDA has recently approved dupilumab as the only treatment for PN, but it is unknown to what extent within-patient categorical improvements in itch and skin lesions occurred concurrently or independently. Two phase 3 clinical trials, LIBERTY-PN PRIME and PRIME2, demonstrated dupilumab efficacy and safety in patients with PN. To report the efficacy of dupilumab on signs and symptoms in adult patients with PN who did and did not achieve the multicomponent endpoint. LIBERTY-PN PRIME (NCT04183335) and PRIME2 (NCT04202679) were randomized, double-blind, placebo-controlled, multicentre, parallel-group, phase 3 trials in adult patients with PN with ≥20 PN lesions and severe itch, inadequately controlled with topical prescription therapies or for whom these are inadvisable. Here, data were pooled from the two studies. Patients received 300 mg dupilumab subcutaneously (600 mg loading dose; n = 153) or matched placebo ( n = 158) every 2 weeks for 24 weeks. This abstract assesses efficacy in patients who did and those who did not achieve the stringent multicomponent endpoint of ≥4-point improvement from baseline in Worst Itch Numerical Rating Scale (WI-NRS, range: 0–10) and Investigator's Global Assessment PN Stage (IGA PN-S, score range: 0–4) score 0 or 1 (clear or almost clear; defined as 5 or fewer nodules) at week 24. Endpoints include a proportion of patients with concomitant ≥4-point reduction in WI-NRS from baseline and IGA PN-S score 0 or 1 at week 24; the proportion of patients with ≥4-point reduction in WI-NRS from baseline or IGA PN-S score 0 or 1 at week 24; and proportion of patients not achieving ≥4-point reduction in WI-NRS from baseline and IGA PN-S score 0 or 1 at week 24. Safety was also assessed. Baseline demographic and clinical characteristics were generally balanced between subgroups. The proportion of patients treated with dupilumab and placebo who achieved the multicomponent endpoints was 35.3% and 8.9%, respectively; and who achieved WI-NRS reduction of ≥4 points from baseline or IGA PN-S score 0 or 1 at week 24 was 69.9% and 27.2%, respectively. Among multicomponent nonresponders in the dupilumab group ( n = 99), 36.4% achieved WI-NRS reduction of ≥4 points and 17.2% achieved IGA PN-S score 0 or 1; in the placebo group ( n = 144), corresponding values were 11.1% and 9.0%, respectively. In the dupilumab group, 23.5% achieved only WI-NRS ≥4-point reduction from baseline at week 24, and 11.1% achieved only IGA PN-S score 0 or 1 at week 24. In the placebo group, corresponding data were 10.1%, and 8.2%, respectively. Safety findings were consistent with the known dupilumab safety profile. More than one-third of dupilumab-treated patients achieved the multicomponent endpoint at week 24, constituting concurrent responses on both itch and skin lesions. However, more than two-thirds had clinically meaningful improvement by week 24, defined as either ≥4-point reduction in WI-NRS from baseline, IGA PN-S score 0/1, or both. Almost one-quarter of dupilumab-treated patients met only WI-NRS ≥4-point improvement at week 24, suggesting that skin lesion improvement may lag behind the improvement of itch. Conversely, one-ninth met only IGA PN-S score of 0 or 1 at week 24 suggesting that, in addition to the overlapping mechanisms by which dupilumab ameliorates pruritus and skin lesions, there are independent treatment effects on itch and skin remodelling. Safety was consistent with the known safety profile of dupilumab across approved indications.